THE IMPACT OF EMOTIONAL STRESS ON THE PHYSICAL AND TECHNICAL PREPARATION OF FOOTBALL PLAYERS: THE IMPACT OF EMOTIONAL STRESS ON THE PHYSICAL AND TECHNICAL PREPARATION OF FOOTBALL PLAYERS - abdullayev, dilshod (Физическое воспитание, спорт и здоровье, 2025)
Based on a theoretical analysis of the literature, the content of the concept of "stress" is determined, internal and external stress factors of sports activities and their manifestations are identified, as well as the development of creative abilities and the use of various methods of mental self-control are recommended.